Surgical treatment for liver cancer - Tsim, Nicole C (Baishideng, 2010)
Primary liver cancer is amongst the commonest tumors worldwide, particularly in parts of the developing world, and is increasing in incidence. Over the past three decades, surgical hepatic resection has evolved from a high risk, resource intensive procedure with limited application, to a safe and commonly performed operation with a range of indications. This article reviews the approach to surgical resection for malignancies such as hepatocellular cancer, metastatic liver deposits and neuroendocrine tumors. Survival data after resection is also reviewed, as well as indications for curative resection.